A specific immune and lymphatic profile characterizes the pre-metastatic state of the sentinel lymph node in patients with early cervical cancer. (1st February 2017) - Balsat, Cédric; Blacher, Silvia; Herfs, Michael; Van de Velde, Maureen; Signolle, Nicolas; Sauthier, Philippe; Pottier, Charles; Gofflot, Stéphanie; De Cuypere, Marjolein; Delvenne, Philippe; Goffin, Frédéric; Noel, Agnès; et al.
ABSTRACT: The lymph node (LN) pre-metastatic niche is faintly characterized in lymphophilic human neoplasia, although LN metastasis is considered as the strongest prognostic marker of patient survival. Due to its specific dissemination through a complex bilateral pelvic lymphatic system, early cervical cancer is a relevant candidate for investigating the early nodal metastatic process. In the present study, we analyzed in-depth both the lymphatic vasculature and the immune climate of pre-metastatic sentinel LN (SLN), in 48 cases of FIGO stage IB1 cervical neoplasms. An original digital image analysis methodology was used to objectively determine whole slide densities and spatial distributions of immunostained structures. We observed a marked increase in lymphatic vessel density (LVD) and a specific capsular and subcapsular distribution in pre-metastatic SLN when compared with non-sentinel counterparts. Such features persisted in the presence of nodal metastatic colonization. The inflammatory profile attested by CD8 +, Foxp3, CD20 and PD-1expression was also significantly increased in pre-metastatic SLN. Remarkably, the densities of CD20 + B cells and PD-1 expressing germinal centers were positively correlated with LVD. All together, these data strongly support the existence of a pre-metastatic dialog between the primary tumor and the first nodal relay. Both lymphatic and immune responses contribute to the elaboration of a specific pre-metastatic microenvironment in human SLN. Moreover, this work provides evidence that, in the context of early cervical cancer, a pre-metastatic lymphangiogenesis occurs within the SLN (pre-metastatic niche) and is associated with a specific humoral immune response.